A CRITICAL DISCOURSE ANALYSIS ON THE POLITENESS STRATEGY IN SOFIA THE FIRST BY CRAIG GERBER - Putri Jesika Lumban Raja; Jenie Posumah; Delli Sabudu (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2024)
In everyday life, identity is expressed through language, interaction, and communication patterns. This study investigates how discourse features shape Princess Sofia’s identity in Sofia the First. This study use Fairclough’s Critical Discourse Analysis (CDA) and Brown and Levinson’s Politeness Strategy framework. This study employed a qualitative research method with a discourse analysis design. The researcher selected Episodes 1–10 of Season 1 based on themes of identity formation and language use. The selected episodes were carefully observed to identify scenes that show character interaction, development, and situations related to power and politeness. After identifying relevant scenes, the researcher transcribed the dialogues. It producing around 450 utterances categorized into Bald-on-Record, Positive Politeness, Negative Politeness, and Off-Record strategies. The findings show that Bald-on-Record dominates, reflecting Sofia’s assertiveness, leadership, and direct problem-solving style. Positive and Negative Politeness appear when Sofia builds relationships, expresses empathy, and navigates social boundaries, while Off-Record strategies emerge in delicate or indirect situations. Through CDA, Sofia’s discourse reveals not only linguistic choices but also the influence of narrative practices and social values such as kindness, equality, responsibility, and emotional awareness. This study contributes to discourse and linguistic studies by showing how politeness strategies in children’s animation construct social roles and power relations. It also highlights the role of media language in shaping children’s understanding of identity, gender norms, and social values, and provides insights for educators and content creators in developing more meaningful and responsible children’s media.